A newborn with a rare association of various congenital skin disorders - Answer - Federico Mecarini; Dario Alario; Giorgio Bracaglia (Hygeia Press di Corridori Marinella, 2022)
We report a female newborn with a combination of 3 skin lesions: Mongolian spots, port-wine stains, and cutis marmorata telangiectatica congenita. This association is an unclassifiable form of phacomatosis and only 7 similar cases have been published in the literature. According to some authors, this association should be considered as a distinct entity of phacomatosis pigmentovascularis (PPV) with the specific name "phacomatosis cesioflammeo-marmorata". PPV pathogenesis is still unclear.